Pendirian Desa Wisata Berkelanjutan di Kalimantan Barat, Indonesia: Sebuah Studi Kasus Desa Wisata Berkelanjutan Pentek di Kabupaten Mempawah - Ningtias, Kartika; Sudagung, Adityo Darmawan; Sari, Venisa Yunita; Adiwinata, Yudha Kusuma (Centre For Tourism Planning and Development, 2024)
The present study aims to explain the formulation and implementation of the tourism village policy in West Kalimantan, Indonesia. The existing tourism village policy and the fact that the village is centred on the national development agenda in Indonesia has shifted more attention towards all villages. By doing explanatory qualitative research through interviews, observation, and literature study at Pentek Sustainable Tourism Village in Mempawah Regency from August to October 2021,this research discovered that the tourism village manager can improve the management of natural, historical, and cultural tourism potential. Our finding showed that Pentek Tourism Villages' condition is classified as embryonic. However, according to social capital concept, the synergy between the government and the community can be an asset for accelerating the development of sustainable tourism villages in the future. Thus, this paper suggests a thorough review of Pentek Sustainable Tourism Village's available potential and resources, increased cross-sectoral collaboration that involves the community, the use of information technology to promote tourism villages, and conducting comparative studies from best practices of other national and international tourism villages.